POWDERED DRINKING WATER TREATMENT RESIDUE ENCAPSULATED BY CALCIUM ALGINATE FOR CONGO RED DYE ADSORPTION - LESTARI NIM:10513068, ANDINI
Dye of textile industry is one of causes for aquatic ecosystem pollution. One of the most widely used dyestuffs in industry such as printing industry, paper industry, and plastic industry mainly textile industry is congo red dye. Congo red dye is an irritant compound and if exposed for long periods cause carcinogenic. Adsorption is a simple, inexpensive and effective method to adsorb a dye waste. In this research, adsorbent is synthesized from powder of drinking water residue encapsulated with calcium alginate for congo red dye adsorption. Adsorbent tested under many adsorption conditions, such as adsorbent composition, pH of the solution, mass of the adsorbent, congo red concentration and contact time. The optimum adsorbent composition was obtained on the ratio of powdered drinking water residue and calcium alginate is 1:4 (w/w). The result of the adsorption optimization process was achieved by using mass of adsorbent is 0,1 gram, concentration of congo red 600 ppm at pH 4 with 24 hours contact time. The characterization of adsorbent was performed by Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM). The adsorption of congo red by adsorbent is following Langmuir isotherm model with maximum adsorption capacity is 64,516 mg g-1 at 25 oC. Parameter of thermodynamic adsorption showed that adsorption is exothermic and value of ?G(25?C) = 11,144 kJ mol-1, ?G(40?C) = 13,149 kJ mol-1, and ?G(55?C) = 15,154 kJ mol-1, value of ?H= -28,696 kJ mol-1 and value of ?S = 0,134 kJ mol??K????